PENGEMBANGAN E-STORYBOOK BERBANTUAN CANVA DAN BOOK CREATOR PADA MATERI BENTANG ALAM INDONESIA SISWA KELAS III SEKOLAH DASAR - Eka Cecilia; Dwi Cahaya Nurani; Siti Dewi Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media in the form of E-Storybook with the help of Canva and Book Creator applications as two main applications in developing E-Storybook media on Indonesian landscape material for third grade elementary school students. This study uses the Research and Development method with the ADDIE model approach. Data analysis in the study was carried out by analyzing validity data and practicality data analysis. The validation results by the validator on the E-Storybook obtained a total score of 93.53%, the criteria of "Very Valid" and the total score results in the student trial obtained a total score of 97.91%, the criteria of "Very Practical". Based on these two results, it can be concluded that the E-Storybook has been tested for validity and practicality as a learning medium that can be used to help the learning process in the classroom.